Effect of Type of Flooring on Growth Performance of Murrah Buffalo Calves (Indian Journal of Animal Production and Management, 2024)
A total of 18 healthy Murrah buffalo calves of either sex, aged 6-8 months, maintained at Buffalo  Research Station (BRS), Venkataramannagudem, were randomly selected and housed in three  separate pens for a period of 3 months from August to October, 2022. Calves of first group were  reared on concrete flooring (T1), the second group on Rubber mat flooring (T2) and the third group  on soil flooring (T3). At the end of the study, the final mean body weights of calves housed on rubber  mat flooring in T2 group (164.48 ± 1.41) kgs was significantly higher (P < 0.01) than T3(156.23 ±  1.17) kgs and T1(151.53 ± 1.23) kgs. The overall mean ADG, chest girths, height at withers and tail  lengths of the animals differed significantly (P < 0.01) and followed the trend T2 > T3 > T1.
Keywords: ADG; biometry; flooring; growth; Murrah buffalo